2022
DOI: 10.1007/s11270-022-05715-5
|View full text |Cite
|
Sign up to set email alerts
|

Tackling Marine Microplastics Pollution: an Overview of Existing Solutions

Abstract: Microplastics pollution is one of the main environmental challenges of our time, even though microplastics were observed for the first time almost 50 years ago. Microplastics—little plastic fragments smaller than 5 mm in size—are released from bigger plastic objects during their use, maintenance, or disposal. As their release is uncontrolled and mostly uncontrollable, microplastics end up in the environment and are easily transported across the world, polluting nearly every ecosystem, especially the aquatic on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Remediating MP contaminants using nontoxic methods and without major disturbances to the natural water constituents is a major challenge that should begin with a feasibility study [60]. A number of newer technologies that mostly involve filtration have been outlined in a review by Fiore et al [61]. For point source microplastic pollution, the most effective solutions involve upstream actions to eliminate the release into the environment, which often requires binding policies and enforcement [62].…”
Section: Potential Remediation Methodology For Mp Contamination In Su...mentioning
confidence: 99%
“…Remediating MP contaminants using nontoxic methods and without major disturbances to the natural water constituents is a major challenge that should begin with a feasibility study [60]. A number of newer technologies that mostly involve filtration have been outlined in a review by Fiore et al [61]. For point source microplastic pollution, the most effective solutions involve upstream actions to eliminate the release into the environment, which often requires binding policies and enforcement [62].…”
Section: Potential Remediation Methodology For Mp Contamination In Su...mentioning
confidence: 99%
“…Fine plastic particles, added in the form of microbeads to cosmetics (e.g. toothpaste, scrubs, shampoos, eye shadows) and cleaning agents, account for only 2% of all virgin MP (Boucher & Friot 2017, Fiore et al 2022, Zhou et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…MPs are a new global environmental pollutant, widely distributed in oceans, rivers, lakes, sediments, soils, and other environmental media (Fiore et al 2022, Hu et al 2021, Shen et al 2018, and are even found in polar areas (Bergmann et al 2019, Ding et al 2023. MPs have also entered the food chain (Wang et al 2021a).…”
Section: Introductionmentioning
confidence: 99%